Grey-fuzzy algorithm to optimise machining parameters in drilling of hybrid metal matrix composites - Rajmohan, T.; Palanikumar, K.; Prakash, S. (Composites. Part B, Engineering, 2013)
Metal matrix composites (MMCs) are difficult to machine due to their abrasive properties. With the projected widespread application of MMCs, it is necessary to develop an appropriate technology for their effective machining. The present investigation focuses on finding the optimal machining parameters setting in drilling of hybrid aluminium metal matrix composites using the grey-fuzzy algorithm. This proposed algorithm, coupling the grey relational analysis with the fuzzy logic, obtains a grey-fuzzy reasoning grade to evaluate the multiple performance characteristics according to the grey relational coefficient of each performance characteristics. The Taguchi method of experimental design is a widely accepted technique used for producing high quality products at low cost, therefore a L27 3-level orthogonal array is used for the experiments. The optimisation of multiple responses in complex processes is common; therefore, to reduce the degree of uncertainty during the decision making, fuzzy rule-based reasoning is integrated with the Taguchi’s method. The response table, response graph and analysis of variance (ANOVA) are used to find the optimal setting and the influence of machining parameters on the multiple performance characteristics. Experimental results have shown that the required performance characteristics in the drilling process are improved by using this approach.